2018
DOI: 10.18203/2320-1770.ijrcog20181342
|View full text |Cite
|
Sign up to set email alerts
|

Study on umbilical cord arterial blood gas analysis and cord blood lactate levels as predictors for adverse neonatal outcome: an observational study

Abstract: Background: Perinatal asphyxia is a major cause of neonatal and childhood morbidity and mortality. Electronic foetal monitoring is used routinely to know the condition of the baby during Intrapartum period. Normal trace correlates highly with absence of acidemia at birth. Abnormal trace needs further evaluation. In order to better define the metabolic status of the new born, umbilical lactate levels have been measured. Objectives of this study were to determine the validity of umbilical cord blood lactate leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…35 Similar results were reported by another study which observed that cord blood lactate is better predictor of neonatal morbidity and mortality as compared to umbilical artery pH. 37 A recent study has also reported that elevated cord blood LDH levels were significantly associated with increased risk of neonatal mortality. 38 Another similar study found that both cord blood Lactate and pH values help in distinguishing between asphyxiated and non-asphyxiated neonates, but lactate levels were observed to be have a better discriminating power.…”
Section: Tablesupporting
confidence: 71%
“…35 Similar results were reported by another study which observed that cord blood lactate is better predictor of neonatal morbidity and mortality as compared to umbilical artery pH. 37 A recent study has also reported that elevated cord blood LDH levels were significantly associated with increased risk of neonatal mortality. 38 Another similar study found that both cord blood Lactate and pH values help in distinguishing between asphyxiated and non-asphyxiated neonates, but lactate levels were observed to be have a better discriminating power.…”
Section: Tablesupporting
confidence: 71%
“…Foetal monitoring can be done by various methods like intermittent auscultation of foetal heart rate, electronic foetal monitoring in form of cardiotocography (CTG), biophysical profile, modified biophysical profile, contraction stress test, doppler velocimetry foetal scalp blood PH, and serum lactate level. [ 5 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Patil SS et al [20], 1.7% cases had convulsions within the first 24 hours after birth. Similar to our study, this was statistically insignificant.…”
Section: Discussionmentioning
confidence: 89%
“…In a study by Patil SS et al [20] who performed a similar study on 295 women, there was no association between need for NICU stay, acidosis at birth and CTG category.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation